The Role of Geranylgeraniol in Managing Bisphosphonate-Related Osteonecrosis of the Jaw - Chin, Kok-Yong; Ekeuku, Sophia Ogechi; Trias, Anne (Frontiers in Pharmacology, 2022)
Medication-related osteonecrosis of the jaw (ONJ) is a rare but significant adverse side effect of antiresorptive drugs. Bisphosphonate-related ONJ (BRONJ) is the most prevalent condition due to its prevalent use in cancer and osteoporosis treatment. Nitrogen-containing bisphosphonates suppress osteoclastic resorption by inhibiting farnesyl pyrophosphate synthase in the mevalonate pathway, leading to deficiency of substrate for GTPase prenylation. The bone remodelling process is uncoupled, subsequently impairing bone healing and ONJ. Therefore, targeted administration of geranylgeraniol (GGOH) represents a promising approach to mitigate BRONJ because it is a substrate for GTPase prenylation. In the current review, the in vitro effects of GGOH on osteoclasts, osteoblasts and other related cells of the jaw are summarised. We also present and appraise the current in vivo evidence of GGOH in managing BRONJ in animal models. Lastly, several considerations of using GGOH in the clinical management of BRONJ are highlighted. As a conclusion, GGOH is a promising topical agent to manage BRONJ, pending more research on an effective delivery system and validation from a clinical trial.